2014
DOI: 10.1167/iovs.14-13885
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Cellular Mechanisms That Modulate Trafficking of Frizzled Family Receptor 4 (FZD4) Missense Mutants Associated With Familial Exudative Vitreoretinopathy

Abstract: Defective trafficking resulting in haploinsufficiency is a major cellular mechanism for several missense FEVR-causing FZD4 mutants. Our findings indicate that this trafficking defect might be correctable for some mutants, which may offer opportunities for the development of novel therapeutics approaches for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…13 Likewise, Ells et al 16 Because relatives with the mutations did not have FEVR, the investigators concluded that these are milder mutations that may exacerbate retinopathy in premature infants. A potential mechanism for these milder FZD4 mutations was recently reported by Milhem et al 34 These investigators used confocal immunofluorescence microscopy to demonstrate localization of several FZD4 mutants, including P33S, in the endoplasmic reticulum when expressed in HeLa cells, indicating defective trafficking of the protein to the plasma membrane. They proposed that this defective trafficking may lead to haploinsufficiency of the frizzled-4 protein.…”
Section: Discussionmentioning
confidence: 92%
“…13 Likewise, Ells et al 16 Because relatives with the mutations did not have FEVR, the investigators concluded that these are milder mutations that may exacerbate retinopathy in premature infants. A potential mechanism for these milder FZD4 mutations was recently reported by Milhem et al 34 These investigators used confocal immunofluorescence microscopy to demonstrate localization of several FZD4 mutants, including P33S, in the endoplasmic reticulum when expressed in HeLa cells, indicating defective trafficking of the protein to the plasma membrane. They proposed that this defective trafficking may lead to haploinsufficiency of the frizzled-4 protein.…”
Section: Discussionmentioning
confidence: 92%
“…cac, which encodes a calcium channel, has seven human orthologs that also encode calcium channel subunits, of which CACNA1F has been associated with congenital night blindness (CSNB2A) (78), Aland Island eye disease (AIED) (79,80), and X-linked conerod dystrophy (CORDX3) (81). fz encodes a seven-transmembrane helix containing protein necessary for binding Wnt ligands in the noncanonical Wnt signaling pathway (82) and has 10 human orthologs encoding frizzled class receptors, of which FZD4 is associated with exudative vitreoretinopathy (83). hbn encodes a transcription factor and has four human orthologs, of which PHOX2A has been associated with congenital fibrosis of extraocular muscles, a disorder that affects the muscles that control eye movement and position of the eyes (84,85).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that norrin-Fzd4 signaling affects angiogenesis in the female reproductive system. Markers for angiogenesis and vascular formation are reduced in the corpora lutea of Fzd4 null mice and these mice are infertile 42. Also, Fzd4 mRNA localizes to vessels and stroma surrounding the mouse embryo 43.…”
Section: Role Of Wnt Signaling In Fetal Developmentmentioning
confidence: 97%